Parallel text in the Arabic novel (selected models) - Bakri, Ahlam Mazen; Qasim, Nadir (Journal of Arabic Language Sciences and Literature, 2023)
This study aimed to take up the parallel text and the representative of the surrounding text and its relationship to the text as a try to answer the followings. This study addresses the parallel text and its relationship with Almatan, in selected models of the Arabic novel, for which the researcher relied on the Semiotic Approach, dividing the study into five themes arranged as follows: First theme: Title, Second theme: Cover, Third theme: Dedication, Fourth theme: Export, Fifth Research: Initiation. The researcher found a number of conclusions, the most important of which being that parallel texts did not have a marginal presence. It served both within and outside the text and allowed its artistic aspects and intellectual and philosophical issues to be illuminated. It further facilitates the reader's access to the deep parts of the text, and knowledge of its contents, and helps him/her understand and interpret it. Parallel texts have been able to coincide with the narrative that brings the reader into it from the very beginning of the title through cover, dedication, initiation, and export. Thus, the parallel texts are intellectual formats that are similar to the sematic of the texts. Its importance is evident in the provocation and suspense of the reader to turn the pages of the book and access the text.
Keywords: cover; dedication; export; initiation; parallel text; title